A study on the differences in morphology and corrosion resistance performance between two different bis(2-ethylhexyl) phosphate self-assembled thin films prepared on an iron substrate in water and ethanol solvents. Issue 61 (10th June 2016) - Yan, Ru; Gao, Xiang; Lv, Dandan; Ma, Houyi
Abstract : BEPE SAMs formed on the iron surface by both electrostatic interaction and chemical covalent binding with island-like surface morphology, while the BEPW SAMs formed only through P–O–Fe bond with nodule-like appearance. Abstract : Bis(2-ethylhexyl) phosphate (BEP) self-assembled thin films were prepared on iron substrates in water and ethanol solutions respectively and the formation mechanisms were investigated by means of attenuated total reflectance-Fourier transform infrared spectroscopy (ATR-FTIR), X-ray photoelectron spectroscopy (XPS) and atomic force microscopy (AFM). For the iron samples treated with BEP aqueous and alcoholic solutions, the appearance of characteristic functional groups in the ATR-FTIR spectra indicated the existence of BEP molecules on the iron surface. XPS results further demonstrated that, BEP molecules bound to the iron surface in different ways in the case of water and ethanol as solvents, leading to the formation of two types of self-assembled monolayers (SAMs). In the ethanol solution, the BEP SAMs formed on the iron surface by both electrostatic interaction and chemical covalent binding, denoted as BEPE SAMs; in the aqueous solution, the BEP SAMs formed on the iron surface only through P–O–Fe (substrate) bond between iron substrate and BEP molecules, denoted as BEPW SAMs. The BEPE SAMs showed an island-like surface morphology, while BEPW SAMs had a nodule-like appearance. When used as ultrathin coatings for corrosion protection, the great differences in microstructure, morphology and compactness between the two BEP SAMs had a strong influence on their anti-corrosive properties, which in turn led to an interesting phenomenon that BEPW SAMs showed much better corrosion protection ability than BEPE SAMs under otherwise identical conditions.